Clinical effect and follow-up of laparoscopic radical proximal gastrectomy for upper gastric carcinoma - Meng, Wei; Ya-di, Huang; Wei-bo, Cao; Ru-dong, Zhao; Ze-wei, Cheng; Ou Yang, Jun; Ze-peng, Yan; Chuan-qi, Chen; Yi-ze, Liang; Dan-ping, Sun; Wen-bin, Yu (Frontiers in Oncology, 2023)
Objective To evaluate the safety and clinical effect of tubular esophagogastric anastomosis in laparoscopic radical proximal gastrectomy. Methods A retrospective analysis was conducted involving 191 patients who underwent laparoscopic radical proximal gastrectomy in the Department of Gastrointestinal Surgery, Qilu Hospital of Shandong University from January 2017 to October 2020. Patients were divided into tubular esophagogastric anastomosis group (TG group) and traditional esophagogastric anastomosis group (EG group) according to the digestive tract reconstruction. Their intraoperative conditions, perioperative recovery and postoperative follow-up were compared. Patients were also divided into indocyanine green group and non-indocyanine green group according to whether or not indocyanine green tracer technology was used during the operation. Their intraoperative condition and perioperative recovery were compared and analyzed after propensity score matching. Results The operation was successfully completed in all patients. Compared with the EG group, the TG group had less volume of gastric tube drainage, shorter gastric tube drainage time and proton pump inhibitors application time, and lower reuse rate of proton pump inhibitors. However, the TG group had a higher anastomotic stenosis at three months after surgery, as measured using anastomotic width and dysphagia score. Nevertheless, the incidence of reflux esophagitis and postoperative quality of life score in the TG group were lower compared with the EG group at 1st and 2nd year after surgery. In the indocyanine green analysis, the indocyanine green group had significantly shorter total operation time and lymph node dissection time and less intraoperative blood loss compared with the non-indocyanine green group. However, compared with the non-indocyanine green group, more postoperative lymph nodes were obtained in the indocyanine green group. Conclusion Laparoscopic radical proximal gastrectomy is safe and effective treatment option for upper gastric cancer. Tubular esophagogastric anastomosis has more advantages in restoring postoperative gastrointestinal function and reducing reflux, but it has a higher incidence of postoperative anastomotic stenosis compared with traditional esophagogastrostomy. The application of indocyanine green tracer technique in laparoscopic radical proximal gastrectomy has positive significance.